Mozart or Pelé? The effects of teenagers` participation in music and sports - Cabane, C.; Hille, A.; Lechner, M. (Discussion Paper Series, 2015)
Using data from the German Socio-Economic Panel, this paper analyses the effects of spending part of adolescents` leisure time on playing music or doing sports, or both. e find that while playing music fosters educational outcomes compared to doing sports, particularly so for girls and children from more highly educated families, doing sports improves subjective health. For educational outcomes, doing both activities appeared to be most successful. The results are subjected to an extensive robustness analysis including instrumental variable estimation and a formal sensitivity analysis of the identifying assumptions, which does not reveal any serious problems